Sakral dan Profan dalam Ritual Life Cycle : Memperbincangkan Fungsionalisme Emile Durkheim - Asliah Zainal (Al-Izzah, 2014)
Abstract In various societies, ritual manifest in almost all stages of human life. It starts from the conception period; birth, childhood, marriage, death, even after the man was die. With the ritual, people try to bring the world and at the same time separate the sacred and the profane one. This paper shall discuss the life cycle rituals in society in Emile Durkheim’s theory of functionalism. In Durkheim’s point of view, society has two sides in their life; time to work and time celebrate the sacred ritual. The dualism of life is what Durkheim called "The sacred" and "The profane". Durkheim considers The Sacred is everything a superior, powerful, and in the normal circumstances, it untouched and honored. Instead of the profane is part of everyday life and mundane. Although the function of ritual is to approach the sacred One, there are social functions within. Therefore, it has the social value in the sense it could strengthen social solidarity among community members. Life cycle rituals provide facilities for every person to feel the religious emotion and feel the presence of the Sacred. Ritual in some cultures, not only a religious obligation but also running efforts to achieve social cohesion as part of a community in which he lives. Keywords: Ritual Life-cycle, Sacred and Profane, Emile Durkheim, Funcsionalism